The metabolic signatures of cardiometabolic diseases: Does the shared metabotype offer new therapeutic targets? - Arwa M. Amin (Wiley, 2021)
Abstract Cardiometabolic diseases (CMDs) are the most common, noncommunicable diseases that claim many lives every year. CMDs have great impact on public health, often driving the attention of healthcare resources to prevent and treat them. CMDs include cardiovascular diseases, type 2 diabetes mellitus, metabolic syndrome, and obesity. Deep understanding of the root causes and pathogenic factors of CMDs would help in their effective prevention and treatment. Metabolomic profiling of biosamples usually sheds light on the metabolic biomarkers and the involved pathways. Metabolomic analysis to identify CMDs metabotypes revealed that they share similar metabolic signatures and metabolic pathways. These metabolic pathways may indicate the presence of insulin resistance, mitochondrial dysfunction, low‐grade inflammation, and dysbiotic gut microbiota. This study is aimed to review the literature on the common metabolic biomarkers of CMDs as well as the shared pathways that can be targeted by dietary interventions and pharmacologic treatment.